2020
DOI: 10.1186/s12884-020-03298-9
|View full text |Cite
|
Sign up to set email alerts
|

Quad test for fetal aneuploidy screening as a predictor of small-for-gestational age fetuses: a population-based study

Abstract: Background To identify the relationship between quadruple test for aneuploidy screening (alpha-fetoprotein: AFP; free beta-human chorionic gonadotropin: b-hCG; unconjugated estriol: uE3 and inhibin-A: IHA) and fetal growth restriction and to construct predictive models for small-for-gestational-age (SGA) fetuses. Methods Women who underwent quadruple test for aneuploidy were followed-up for final outcomes. The multiples of the median (MoMs) of the four biochemical markers for the SGA group and those of norma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In previous reports, high hCG in maternal blood has been observed from early pregnancy in patients with FGR and PE 9 – 11 . Therefore, we first investigated whether hCG was also elevated in the postnatal placentas of these patients.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In previous reports, high hCG in maternal blood has been observed from early pregnancy in patients with FGR and PE 9 – 11 . Therefore, we first investigated whether hCG was also elevated in the postnatal placentas of these patients.…”
Section: Resultsmentioning
confidence: 83%
“…hCG is produced by syncytiotrophoblasts (STB) and peaks between the 7th and 10th weeks of pregnancy, with a nadir at 18th weeks 8 . Several studies have demonstrated that patients with FGR and PE exhibit higher blood levels of hCG from early pregnancy until before delivery 9 – 11 , and placental dysfunction may reflect the increased hCG levels 12 15 . Therefore, we speculated that high hCG is a risk factor for the development of FGR and PE.…”
Section: Introductionmentioning
confidence: 99%
“…AFP is then transported to maternal serum through the placenta or by diffusion across fetal membranes [15,16]. Elevated msAFP values are found to be associated with the fetalmaternal-placental barrier disruption, placental vascular damage or bleeding, or feto-placental ischemia and can compromise the development of a structurally normal fetus [16,17]. The relationship between the AFP increase in the second trimester and pregnancy complications (such as gestational hypertension, preeclampsia, fetal loss, preterm delivery, IUGR, placental abruption, and bleeding) has also been established [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated msAFP values are found to be associated with the fetal-maternal-placental barrier disruption, placental vascular damage or bleeding, or feto-placental ischemia and can compromise the development of a structurally normal fetus [ 16 , 17 ]. The relationship between the AFP increase in the second trimester and pregnancy complications (such as gestational hypertension, preeclampsia, fetal loss, preterm delivery, IUGR, placental abruption, and bleeding) has also been established [ 14 - 17 ]. Therefore, the link between AFP increase and IUGR yielded by our analyses is supported by empirical evidence [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combination of the clinical, biochemical, and biophysical markers is likely to increase the predictive power of screening examinations [ 36 ]. Currently, the implementation of serum biomarker screening quad test (AFP, alpha-fetoprotein; BHCG, beta-human gonadotropin; uE3, unconjugated estriol; and IHA, inhibin-A) for fetal aneuploidy has commenced worldwide, and many studies have shown that additional information derived from such screenings, other than aneuploidy risk estimation, can also be used to identify the risk of adverse obstetric outcomes, such as fetal growth restriction, PE, and preterm birth [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%